2018
DOI: 10.1136/bmjdrc-2017-000499
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prediction model for insulin-associated hypoglycemia in non-critically ill hospitalized adults

Abstract: ObjectiveTo develop and validate a multivariable prediction model for insulin-associated hypoglycemia in non-critically ill hospitalized adults.Research design and methodsWe collected pharmacologic, demographic, laboratory, and diagnostic data from 128 657 inpatient days in which at least 1 unit of subcutaneous insulin was administered in the absence of intravenous insulin, total parenteral nutrition, or insulin pump use (index days). These data were used to develop multivariable prediction models for biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 32 publications
(29 reference statements)
3
43
0
Order By: Relevance
“…Another possible reason to this relation is that patients who require a higher amount of insulin could have an underlying condition causing insulin resistance. A prediction model established that the risk of hypoglycemia is directly proportional to increases in the total insulin dose until reaching a threshold of 0.8 units/kg where this relationship can no longer be observed [ 25 27 ]. Studies with a greater sample that show a stronger association are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possible reason to this relation is that patients who require a higher amount of insulin could have an underlying condition causing insulin resistance. A prediction model established that the risk of hypoglycemia is directly proportional to increases in the total insulin dose until reaching a threshold of 0.8 units/kg where this relationship can no longer be observed [ 25 27 ]. Studies with a greater sample that show a stronger association are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Coefficient of variation and standard deviation of glucose measures calculated by CGM have been described as ways of representing glycemic fluctuation. Diverse studies have demonstrated the association between the coefficient of variation and adequate control of HbA1C or presence of hypoglycemia [ 27 29 ]. By prediction models, it has been established that for every 10% increase in the value of coefficient of variation, risk of hypoglycemia increases by 19% [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathioudakis et al established a prediction model for insulinassociated hypoglycemia in non-critically ill hospitalized adults. The model is based on multiple variables including mean BG, nadir BG, BG coefficient of variation, age, weight, diet status, insulin doses, types of diabetes, stage of chronic kidney disease, and liver function [25]. The sensitivity and specificity of this model were 81.9% and 78.6%.…”
Section: Discussionmentioning
confidence: 99%
“…6 Many factors contribute to hypoglycaemia among hospitalized patients, including increasing age, higher insulin doses, basal insulin, mistiming of insulin administration, lower body weight, decreased renal function, and changes in diet or medications. 7 Hypoglycaemia in the hospital is associated with longer length of stay, increased inpatient and 1-year mortality, and increased costs. 8 In ambulatory settings, HF is associated with increased risk of severe hypoglycaemia.…”
mentioning
confidence: 99%